2020
DOI: 10.3389/fpsyg.2020.01359
|View full text |Cite
|
Sign up to set email alerts
|

Dropout, Autonomy and Reintegration in Spain: A Study of the Life of Young Women on Temporary Release

Abstract: This study analyses the psycho-educational and social paths of women prisoners after the time they drop out of school as minors, based on different variables related to autonomy and their preparedness to face temporary release. Methods: Qualitative and quantitative methods were used to analyse a national sample of 310 women prisoners (30.1% of the population) in 31 prisons through a mixedmode questionnaire and interview. We analysed the significant association of variables related to dropout and obtained a log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
(72 reference statements)
0
6
0
6
Order By: Relevance
“…Providing these women with adequate opportunities for professional training during incarceration can help them get a job after serving their sentence, thus facilitating social reintegration and breaking the cycle of social vulnerability and violence. Managers must know that the training and the possibility of employment can correspond to market demands and aim to increase these women's actual chances of earning a decent wage after imprisonment 3,15,16 .…”
Section: Ngo -Cnseg Training and Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Providing these women with adequate opportunities for professional training during incarceration can help them get a job after serving their sentence, thus facilitating social reintegration and breaking the cycle of social vulnerability and violence. Managers must know that the training and the possibility of employment can correspond to market demands and aim to increase these women's actual chances of earning a decent wage after imprisonment 3,15,16 .…”
Section: Ngo -Cnseg Training and Gendermentioning
confidence: 99%
“…The Brazilian Penitentiary System, in general, does not prioritize a policy with a gender approach due to its various deficiencies, which causes gaps in the social reintegration of women deprived of their liberty. The gender approach is vital so that the particularities of women can be considered in the social reintegration measures offered by governmental and non-governmental institutions [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, other studies have shown that women inmates typically have low or medium-level education and follow cultural and educational paths with many disadvantages before going to prison [1,57], with 30% of women inmates in prison regimes having no education and 40% of women having only completed primary school [58]. Similarly, 66.6% of the young women left the education system as minors (primary 49.3% and secondary 22%), becoming more vulnerable than those who stayed in school to adult age [59].…”
mentioning
confidence: 99%
“…As to the relationship between formal education and attending training courses, Añaños et al [59] show that training in prison can become an opportunity to increase prosocial attitudes, improve emotional wellbeing, and decrease the risk of unemployment. These opportunities become the starting point for preparing for life in freedom.…”
mentioning
confidence: 99%
“…On the other hand, the period of incarceration in an ordinary regime is considered a conditioning factor by the majority of open regime professionals with positive convictions in the reintegration process (94.3%), who consider that incarceration in penal units is a mechanism of social vulnerability and exclusion that hinders reintegration [3,10,17,36]. In response, the Prison Institution introduces the open regime (3rd degree and 2nd degree art.…”
mentioning
confidence: 99%